Between Artificial Intelligence, Humans, and Religious Activities (Oratio Directa, 2023)
Artificial intelligence has entered not only public spaces but also private and religious activities. Religious communities increasingly use AI-supported applications, robotic clergy, and generated sermon material in worship. This qualitative descriptive study examines the diffusion of AI into religious practice and its implications for relations among worshippers, religious leaders, and God. The analysis draws on conceptual literature, documented examples from Buddhist, Christian, and Muslim practices, and diffusion of innovations theory. The study finds that AI can improve efficiency and assist repetitive or informational aspects of worship, but it cannot fully replace the psychological, emotional, moral, and non-material relationships embodied by human religious leaders. Unrestricted substitution may weaken religious authority and the emotional quality of worship. AI should therefore remain a supporting instrument governed by religious and human values rather than become the dominant actor in religious practice.
Keywords: Artificial intelligence; Religious activities; Diffusion of innovations; Religious leaders; Human-technology relations